Chemical composition of sage (Salvia officinalis L.) essential oil from the Rio de Janeiro State (Brazil) - Porte,A. (2013)
The purpose of this study was to investigate the chemical composition of the essential oil from fresh leaves of sage (Salvia officinalis L.) from Petrópolis, Rio de Janeiro State, for international trade. The oil was isolated by hydrodistillation in a Clevenger-type apparatus and analyzed through a combination of GC-FID and GC-MS. The yield was 2.3 % on dry basis. Forty-seven constituents were identified according to their chromatographic retention indices and mass spectra, corresponding to 94.90 % of the compounds present. The major constituents of the oil were α-thujone (40.90 %), camphor (26.12 %), α-pinene (5.85 %) and β-thujone (5.62 %). The essential oil studied was similar to those found in several European countries and can be a valuable product for the small farmers from the Petrópolis region in Rio de Janeiro State.